2020
DOI: 10.5194/hess-2020-575
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Camera-based Water Stage and Discharge Prediction with Machine Learning

Abstract: Abstract. Time-lapse imagery of streams and rivers provide new qualitative insights into hydrologic conditions at stream gauges, especially when site visits are biased toward baseflow or fair-weather conditions. Imagery from fixed, ground-based cameras is also rich in quantitative information that can improve streamflow monitoring. For instance, time-lapse imagery may be valuable for filling data gaps when sensors fail and/or during lapses in funding for monitoring programs. In this study, we automated the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The three position markers implemented in the structure of QR‐Codes allows the recognition of the marker in images independent of their location on the actual image (Pandya & Galiyawala, 2014). Using QR‐Codes as a fiducial marker thus does neither require the detection of a water line on the image, nor does it require the definition of a region of interest as it is often required image‐based water level measurement (Chapman et al, 2020; Eltner et al, 2021; Kuo & Tai, 2022; Young et al, 2015; Zhang et al, 2019). Another advantage of QR‐codes is that they are still readable if part of them are not well visible.…”
Section: Methodsmentioning
confidence: 99%
“…The three position markers implemented in the structure of QR‐Codes allows the recognition of the marker in images independent of their location on the actual image (Pandya & Galiyawala, 2014). Using QR‐Codes as a fiducial marker thus does neither require the detection of a water line on the image, nor does it require the definition of a region of interest as it is often required image‐based water level measurement (Chapman et al, 2020; Eltner et al, 2021; Kuo & Tai, 2022; Young et al, 2015; Zhang et al, 2019). Another advantage of QR‐codes is that they are still readable if part of them are not well visible.…”
Section: Methodsmentioning
confidence: 99%
“…The latter is particularly important in cases or areas where establishing a stage-discharge rating curve is difficult, when possible at all. Research reported on image-based hydrological monitoring tends to either focus on Large Scale Particle Image Velocimetry (LS-PIV) to compute discharge [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], on discharge measurements using machine learning [29], on flood detection from surveillance cameras [30][31][32][33], or, on the stage measurement itself [2,[34][35][36][37][38][39][40][41][42][43] from which discharge is often calculated.…”
Section: Introductionmentioning
confidence: 99%